PERANAN MASYARAKAT DALAM PENGEMBANGAN OBJEK WISATA ALAM DANAU NINIFALA DESA PILIANA KABUPATEN MALUKU TENGAH - Yusdi Y.R.S Mahulete; Henderina Lelloltery; Billy B. Seipalla (JURNAL HUTAN PULAU-PULAU KECIL, 2020)
The objectives of this study were to identify the potential of natural tourism of Lake Ninifala and determine the communities roles on managing and developing Lake Ninifala tourism object. The method used was survey with interview, observation, and documentation data collection techniques. Community sampling was used purposive sampling technique. Analysis of the data used descriptive qualitative analysis. The results showed the potential of the lake ninifala tourism object, including the potential of flora and fauna which has the uniqueness and natural beauty in the form of two trees in the middle of the lake called "match water". The community plays a role in providing tourist facilities such as building gazebos, walking places and stalls / kiosks. The role of the community in the aspect of accessibility is in the form of repairing damaged roads and making new roads to the location of objects and the role of the community in providing tour guides. The role of BUMDES in tourism activities includes the role in the planning aspect, related to decision making in the form of giving ideas and opinions about the management of attractions. The area management aspects such as the community provides the facilities needed by tourists, the cleanliness of tourist sites and tree planting activities around the lake. The utilization aspect of economic value such as people earn income from tourist spending and social cultural values ​​in the form of community pride agains their tourism potential. Furthermore, the community and BUMDES together become supervisors.